Case Report: Combined PD-1 and tyrosine kinase blockade stabilizes refractory pancreatic cancer guided by the spatial structure of tumor immune microenvironment - Yang, Heqi; Ma, Yuhang; Zhang, Chenyan; Leng, Qingqing; Cheng, Ke; Zhao, Chengjian; Cao, Dan (Frontiers in Immunology, 2025)
Pancreatic cancer is characterized by a poor prognosis and limited responsiveness to conventional therapies, presenting a substantial therapeutic challenge. Although chemotherapy remains the cornerstone of systemic treatment, options become scarce once frontline therapies fail. While targeted therapies and immunotherapies have emerged as potential alternatives, their efficacy in pancreatic cancer is not well established. As research advances, exploring the tumor immune microenvironment (TiME) of pancreatic cancer is crucial and holds significant potential for developing novel treatment strategies.We report a case of a pancreatic cancer patient who, after the failure of frontline and second-line treatments, was treated with a pioneering combination of targeted therapy and immunotherapy to modulate the unique TiME. The targeted agent, surufatinib, is a tyrosine kinase inhibitor (TKI) that targets vascular endothelial growth factor receptor (VEGFR) 1–3, fibroblast growth factor receptor 1 (FGFR1), and colony-stimulating factor 1 receptor (CSF-1R). The immunotherapy agent, toripalimab, is an immune checkpoint inhibitor targeting programmed cell death protein 1 (PD-1). Remarkably, the patient benefitted from this regimen, exhibiting stable disease, improved clinical symptoms, and prolonged progression-free survival. This case highlights the potential of personalized therapy in treating pancreatic cancer, particularly in patients with distinctive features of the TiME that may predict favorable responses to immunotherapy. Personalized strategies that consider the spatial structure and composition of the TiME may offer a promising avenue for achieving long-term progression-free survival in patients with pancreatic cancer.